Superman - The Lost Episodes - Sparber, Isidore; Gordon, Dan; Kneitel, Seymour (Winstar, 1999)
"Superman - The Lost Episodes" were produced after the demise of Fleischer Studios and the exit of Dave Fleischer. Unlike the first nine episodes (Max Fleischer's Superman) these eight are far more modern. They were all produced in Famous Studios' New York facilities. They are among the best animation ever created. Seen here in fully restored color and with gut-wrenching additional music and Feel the Sound effects, prepare yourself for the animated ride of your life! [Cover]
Keywords: DVD-Video